Construction and Performance Research of Reinforced Iron-Based Powder Metallurgy Materials Based on Phyllanthin as Drug Transport Carriers - Xuehua Feng; Ali Tao; Zurong Song (Advances in Materials Science and Engineering)
Iron-based powder metallurgy materials are the largest type of powder metallurgy materials, mainly used in structural parts, bearings, and friction materials. Iron-based powder metallurgy materials have a series of advantages such as low cost, good machinability, good weldability, and heat treatment. In recent years, the enhanced iron-based powder metallurgy materials based on lavender elements have become a hot spot in the development of material transportation carriers. In order to study the effects of different hot pressing and sintering temperatures on the density, microstructure, and hardness of the enhanced iron-based powders of caladium, we conducted related studies on the structure core properties of the enhanced iron-based powders of caladium to explore whether it can be used as a drug transport carrier. The research results show that hot pressing sintering can make the powder achieve high densification at lower temperature and shorter cycle, especially in the preparation of difficult-to-form and sintered powder metallurgy materials with unique advantages.